Community-Based Supports and Services for Older Adults: A Primer for Clinicians. (1st February 2015) - Siegler, Eugenia L.; Lama, Sonam D.; Knight, Michael G.; Laureano, Evelyn; Reid, M. Carrington
Abstract : Although 20% of adults 60 years and older receive community-based supports and services (CBSS), clinicians may have little more than a vague awareness of what is available and which services may benefit their patients. As health care shifts toward more creative and holistic models of care, there are opportunities for CBSS staff and primary care clinicians to collaborate toward the goal of maintaining patients' health and enabling them to remain safely in the community. This primer reviews the half-century history of these organizations in the United States, describes the most commonly used services, and explains how to access them.